Protótipo de estação meteorológica baseada em WI-FI e banco de dados - Souza, Eberton Cargnin de (2024)
Due to the advancement of current technology, the use of data is becoming increasingly significant. This trend is accompanied by a shift in people's thinking, with a growing number of devices being used to organize time more efficiently. Weather forecasting exemplifies the growing need for quick access to high-quality information. Agriculture is one of the sectors highly dependent on climatic conditions, as precipitation, air temperature, and solar radiation are essential for decisions on planting dates, irrigation, and agricultural production modeling. However, to obtain a weather or climate forecast, in addition to efficient meteorological models, effective surface meteorological stations are essential for understanding the current state of the atmosphere. Despite the good accuracy of current meteorological stations, they have a high cost, primarily due to the need for importing parts and accessories. Motivated by this, the study investigates the creation of a low-cost meteorological station using an ESP32 microcontroller and inexpensive sensors to measure essential meteorological variables such as atmospheric pressure, air temperature, relative humidity, wind speed and direction, global solar radiation, precipitation, and soil temperature. The data measured by the station is transmitted remotely via a Wi-Fi network, stored in a database, and locally on a memory card. The data is displayed in the form of graphs on an online platform, allowing users to filter the information for viewing and downloading based on the selected variable and date. Sensor calibration is performed using statistical methods, comparing them with another field-calibrated standard meteorological station. Preliminary tests have already demonstrated the efficiency of the developed station in terms of system stability over long periods of measurement. At the end of the development and calibration of the meteorological station, it is expected to verify and confirm that the sensors can accurately measure the meteorological variables. Thus, we aim to improve the development method of the meteorological station and potentially commercialize it more economically for meteorological purposes in the future.